Image Selective Segmentation Under Geometrical Constraints Using an Active Contour Approach (Communications in Computational Physics, 2010)
In this paper we propose a new model for segmentation of an image undersome geometrical constraints in order to detect special regions of interest. Our workis based on the recent work by Gout et al. [Numer. Algorithms, 39 (2005), pp. 155-173and 48 (2008), pp. 105-133] using geodesic active contours models, by combining itwith the idea of a piecewise constant Mumford-Shah model as with the non-selectiveChan-Vese segmentation. Numerical tests show that our method is more robust thanthe previous works.